Association between polycystic ovary syndrome and endometrial cancer risk: a systematic review - Alsulayem, Reem A.; Alibrahim, Aseel A.; Alabdulmohsen, Nour A.; Almubark, Hawraa A.; Bukhamsin, Fatimah A.; Almuqarrab, Zahra J.; Almutairi, Razan M.; Alshammari, Haya M.; Alhubail, Rawan M.; Alkhamis, Fatimah H. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Objective of the study was to clarify the relationship between the risk of endometrial carcinoma (EC) and polycystic ovary syndrome (PCOS). Methods: A thorough search across four databases identified 816 relevant publications. After removing duplicates using Rayyan Qatar Computing Research Institute (QCRI) and screening for relevance, 383 full-text articles were reviewed, with 6 studies ultimately meeting the criteria for inclusion. Results: A total of 25,016 women with PCOS diagnoses were involved in six investigations. With a total incidence of 254 (1%), the prevalence of EC among PCOS patients varied from 0.13% to 52%. Patients with PCOS are more likely to get EC, according to many research. The underlying causes are linked to chronic endometrial estrogen stimulation, with contributing factors including hyperlipidemia, diabetes mellitus, and hypertension. These factors increase the chance of EC in women with PCOS. Conclusions: These findings demonstrate the robust correlation between PCOS and a higher risk of EC, emphasizing the need for proactive monitoring and prevention in clinical practice. While the evidence points to significant risk factors such as metabolic disturbances, further research is needed to establish a direct causal link and address potential biases. Nevertheless, integrating cancer risk management into the care of women with PCOS is essential for reducing long-term complications.